2019
DOI: 10.1177/2192568219875121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Insurance Status on Curve Magnitude in Adolescent Idiopathic Scoliosis in Mainland China

Abstract: Study Design: Retrospective cohort study. Objectives: To determine whether there is an association between insurance status and curve magnitude in idiopathic scoliosis pediatric patients in mainland China. Methods: Medical records of patients with adolescent idiopathic scoliosis in 4 tertiary spine centers across China from January 2013 to December 2017 were analyzed. Data was extracted on insurance status, curve magnitude, recommended treatment at presentation, source of referral, and treatment initiated. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Prior research has provided inconsistent results regarding the effect of healthcare disparities on the quality of care for AIS patients due to small sample size, lack of diversity within the study population, and incomplete geographic coverage. [11][12][13][14] These studies tended to isolate one variable, predominantly race or insurance status, without exploring the potential complex interactions between various socioeconomic factors. In the current study, we sought to further assess the interaction of socioeconomic factors on healthcare disparities associated with the treatment of pediatric spine deformity in our previously unstudied geographic region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has provided inconsistent results regarding the effect of healthcare disparities on the quality of care for AIS patients due to small sample size, lack of diversity within the study population, and incomplete geographic coverage. [11][12][13][14] These studies tended to isolate one variable, predominantly race or insurance status, without exploring the potential complex interactions between various socioeconomic factors. In the current study, we sought to further assess the interaction of socioeconomic factors on healthcare disparities associated with the treatment of pediatric spine deformity in our previously unstudied geographic region.…”
mentioning
confidence: 99%
“…Prior research has provided inconsistent results regarding the effect of healthcare disparities on the quality of care for AIS patients due to small sample size, lack of diversity within the study population, and incomplete geographic coverage 11–14. These studies tended to isolate one variable, predominantly race or insurance status, without exploring the potential complex interactions between various socioeconomic factors.…”
mentioning
confidence: 99%
“…Many studies have been conducted to assess the potential risk factors that may contribute to advanced AIS curvature before surgery, including the effects of SES. 2,3,6 There is contention surrounding the topic of SES and AIS curve magnitude. 3,6 It is also unclear what measure of SES is the most accurate to use (eg zipcodes, ADI, and COI).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested a child's socioeconomic status (SES) may affect the timing of when they first present to the orthopaedic clinic. [2][3][4][5] Specifically, children from low SES backgrounds are more likely to experience longer referral times and delays in orthopaedic treatment than those from higher SES backgrounds. [2][3][4][5] Furthermore, Russell et al 3 demonstrated that patients with AIS using government insurance were more likely to present with greater major coronal curve angles than those using private insurance plans, but this was of questionable clinical significance.…”
mentioning
confidence: 99%
See 1 more Smart Citation